Production and Characterization of Monoclonal Antibodies to Japanese Encephalitis Virus - SHIMODA, Hiroshi; Hassan Y. A. H. MAHMOUD; NOGUCHI, Keita; TERADA, Yutaka; TAKASAKI, Tomohiko; SHIMOJIMA, Masayuki; MAEDA, Ken (Journal of Veterinary Medical Science, 2013)
In this study, eighteen monoclonal antibodies (MAbs) to recent Japanese encephalitis virus (JEV) genotype I were produced and characterized by plaque reduction neutralization test, western blot analysis, indirect immunofluorescence assay and enzyme-linked immunosorbent assay. All MAbs recognized only envelope (E) protein or conformational epitope of E and precursor membrane proteins. Two MAbs (7E5 and 3-3H8) possessed virus-neutralization activity, and their escape mutants possessed a change of glutamine to histidine at the position of 52 of E protein, suggesting that these neutralizing MAbs recognize the domain I–II hinge region of E protein. Five MAbs recognized all examined flaviviruses, and two were specific to JEV. These MAbs may be useful for differentiation and diagnosis of flaviviruses.